The diversity of gastropods at intertidal zone cingkuak island and pasumpahan island West sumatra - Manurung, Cici Lestari; Tanjung, Afrizal; ', Elizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This study was conducted in June 2013. The study aim was to the determine the diversityof gastropods in the intertidal zone of Cingkuak Island and Pasumpahan Island. Survey methodwas used to collect information related to the purpose of the study. There were 2 stations chosenalong Cingkuak Island and Pasumpahan Island. For each station there were 3 transects, whichhave 5 plot for every transect, were employed. Sample of gastropods were transported to thelaboratory for identification, counting of the individual number, and calculation of the value ofdiversity index, dominance index and equibility index.The results showed that there were 164 individual gastropods at Cingkuak Island and 90individual gastropods at Pasumpahan Island. The gastropods were comprised of 4 orders, 4families and 16 species. The most dominant species founded in Cingkuak Island andPasumpahan Island were Littoraria intermedia and Littorina vespacea. The value of diversityindex at Cingkuak Island was high and at Pasumpahan Island was medium. Value of equabilityindex was medium. Value of dominance index at Cingkuak Island and Pasumpahan Island waslow. The habitat of gastropods still supported and considered safe for macrozoobhenticorganism.Keywords: Diversity, Gastropods, Cingkuak Island, Pasumpahan Island